Four-year follow-up from the phase 2 study TD-NICE: neoadjuvant treatment of tislelizumab combined with chemotherapy in resectable esophageal squamous cell carcinoma - Yajie Mao; Zhiyuan Gao; Yichen Sun; Changjian Shao; Hongtao Duan; Xiaolong Yan (BMC Cancer)
Abstract Background The efficacy and safety of tislelizumab combined with chemotherapy as neoadjuvant therapy have been presented and evaluated in previously published TD-NICE study. However, the long-term impacts of patients who received tislelizumab plus chemotherapy followed by surgery were not observed in the study. Methods From September 2020 to March 2021, a total of 45 patients were enrolled in the TD-NICE trial. The 4 -year follow-up data of the TD-NICE ITT population were collected by investigators. The primary endpoint was OS, and the secondary endpoint was EFS. Kaplan-Meier method and cox proportional hazards model were used to proceed statistical analysis. Results The median OS and EFS were not reached in all patients. The OS was 82.2% (95%CI:67.6–90.7) at 12 months, 73.3%(95%CI:57.8–83.9) at 24 months, 66.7%(95%CI:50.9–78.4) at 36 months and simulated 66.2% (95%CI:46.5–74.6) at 48 months. There were statistically significant differences between surgery and non-surgery patients(P = 0.046). And patients with R0 resection had a higher improvement in OS than those with R1&R2 resection (P = 0.041). The differences in EFS in surgery and non-surgery group (P = 0.046) as well as in R0 resection and R1&R2 resection group (P = 0.045) were significant, respectively. Discussion Our study identified that chemoimmunotherapy plus surgery could improve overall survival in resectable ESCC, and patients had significant benefits from surgery and R0 tumor resection. Trial registration TD-NICE study was registered in the August 28, 2020, and the registration number was ChiCTR2000037488 (Chinese Clinical Trial Registry (ChiCTR) identifier).